The objective of the study was to analyze the impact of agropolitant program on the regional economy and farmers’ income, and measure the level of people’s participation. The research results show that corn-based agropolitant development has improved the regional economy of Pohuwato Regency through a change in the structure of regional economy and increased the farmers’ income although the major (prioritized) sectors such agriculture, sub-food crops, corn commodities and transportation are stil - Sherly G. Jocom; Eka Intan K. Putri; Himawan Hariyoga (Forum Pasca Sarjana, 2009)
The objective of the study was to analyze the impact of agropolitant program on the regional economy and farmers’ income, and measure the level of people’s participation. The research results show that corn-based agropolitant development has improved the regional economy of Pohuwato Regency through a change in the structure of regional economy and increased the farmers’ income although the major (prioritized) sectors such agriculture, sub-food crops, corn commodities and transportation are still low in competitiveness. The people’s participation in the agropolitant area was at the level of consultation. Key words: agropolitant, regional economy, community’s participation